Evaluation of the vulnerability of components of the water supply system - Sare Roudbari; Mohammadali Nekooie; Roohollah Taherkhani (مهندسی و مدیریت ساخت)
Water infrastructure is a vital vital artery that has always been exposed to natural and man-made threats over the years. This infrastructure is difficult for many people, since it is the center of gravity of a country, it is difficult to imagine life even for a day without water. As a result, governments and authorities must always have plans to reduce the damage to this infrastructure and be fully prepared when incidents occur. One of the measures to reduce the damage to the water network is to assess the vulnerability of all components of the water network to extraction of more critical points in order to allocate more funds to protect that area. In this paper, determining the different sections of the water network determines the extent of their vulnerability and, consequently, the vulnerability of the entire water network.